STK1p Based on the Serum Thymidine Kinase 1 as a Tumour Proliferation Marker Detected for Risk Assessment of Pre-carcinoma to Carcinoma Colorectal Progression: A Meta-Analysis - Hei, Ailian; Li, Jin; Zhou, Ji; He, Ellen; Skog, Sven (New Horizons in Medicine and Medical Research Vol. 8, 2022)
This study aimed at investigating whether serum thymidine kinase 1 concentration (STK1p) based on the TK1-IgY-pAb to assess the progression risk from colorectal adenoma polyp/dysplasia to colorectal carcinoma (CRC). A total of 25 publications containing patients with CRC (n=2,251), patients with colorectal polyp/dysplasia (n=1,165) and tumour-free controls (n=1,887) were analysed in the present meta-analysis. The publications were collected from PubMed, Embase, CENTRAL, CNKI, WanFang, VIP and SinoMed databases from January 1, 2009, until January 31, 2022. Articles were analysed using fixed or random effect models to calculate the mean difference. The Newcastle-Ottawa Scale was used for assessing the quality of collected studies. The meta-analysis followed the PRISMA statement. The results revealed that STK1p significantly distinguished tumour-free individuals from patients with CRC, and from patients with colorectal adenoma polyp/dysplasia (p<0.0001). Meanwhile, STK1p levels decreased by 34.1% within one month following surgery in CRC patients (p<0.0001). No significant publication bias was identified in this study. It was concluded that TK1-IgY-pAb is a reliable biomarker for early detection of colorectal adenoma polyp/dysplasia or pre-cancerous lesions, which may therefore prevent progression into colorectal carcinoma and give the patient a best chance of cure. Combining STK1p with colorectal-associated biomarkers, in addition to the determination of tumour stage and grade may therefore be of use.